2018
DOI: 10.5197/j.2044-0588.2018.037.006
|View full text |Cite
|
Sign up to set email alerts
|

First report of a ‘Candidatus Phytoplasma asteris‘‐related strain (16SrI‐B) associated with Sonchus oleraceus (common sowthistle) phyllody disease in Iran

Abstract: Common sowthistle (Sonchus oleraceus) is a major weed problem in Iran and is also used for medicinal purposes. During 2012-2015 surveys of Fars and Yazd provinces (Iran) for phytoplasma diseases, a phyllody disease was observed in S. oleraceus plants growing as weeds within and/or in the surroundings of fields and orchards. The main symptoms of the disease were yellowing and reddening of leaves, shortened internodes, flower virescence, phyllody, proliferation and witches' broom ( Fig. 1).Total DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In spite of several reports about the presence of aster yellows phytoplasmas (16SrI) in Iran (Babaie et al 2007;Asghari Tazehkand et al 2010;Rashidi et al 2010;Esmailzadeh Hosseini et al 2015a, b, c;Salehi et al 2016Salehi et al , 2018 this is the first phytoplasma affiliated to the 16SrI-R subgroup in the country. This creates a greater awareness of the diversity of phytoplasmas in Iran.…”
Section: Discussionmentioning
confidence: 90%
“…In spite of several reports about the presence of aster yellows phytoplasmas (16SrI) in Iran (Babaie et al 2007;Asghari Tazehkand et al 2010;Rashidi et al 2010;Esmailzadeh Hosseini et al 2015a, b, c;Salehi et al 2016Salehi et al , 2018 this is the first phytoplasma affiliated to the 16SrI-R subgroup in the country. This creates a greater awareness of the diversity of phytoplasmas in Iran.…”
Section: Discussionmentioning
confidence: 90%
“…Phytoplasma groups 16SrI and 16SrVI have broad host plant ranges (Lee et al, 2004;Hiruki et al, 2004), and have also been reported from numerous and different plant hosts in Iran (Babaie et al, 2007;Salehi et al, 2016;2018;Asghari Tazehkand et al, 2010;Rashidi et al, 2010;Esmailzadeh Hosseini et al, 2015, 2017aFattahi et al, 2016). This indicates that various reservoir host plants besides jujube nurseries are likely to be present.…”
Section: Discussionmentioning
confidence: 98%
“…Although three different phytoplasma groups including 16SrI, 16SrII and 16SrV (Marcone et al., ; Neves de Souza et al., ; Salehi et al., ) have been reported from Eucalyptus spp., no difference in the disease symptoms has been described. This confirms that different phytoplasmas may induce identical symptoms in a given plant species (Marcone et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive and accurate detection of phytoplasmas is a prerequisite for the management of their associated diseases. The group 16SrI phytoplasma was previously recorded in E. camaldulensis in eastern Fars, Iran (Salehi, Esmailzadeh Hosseini, & Salehi, ). Based on observed symptoms, the presence of a phytoplasma was suspected during surveys on the E. camaldulensis plant species in western Fars and the Khozestan province in Iran.…”
Section: Introductionmentioning
confidence: 91%